Indigenous Knowledge of the Sea Tribe Society in Panglong Village, Berakit Village, Bintan Island, Riau Archipelago - Putri Yati; Sakila; Nikodemus Niko (PT FORMOSA CENDEKIA GLOBAL, 2022)
The sea tribe in Panglong Village still applies their customary knowledge in their daily lives. The customary knowledge that they applied during their stay is slowly being abandoned as they are laid off on land. This research uses descriptive qualitative. Field data collection by way of observation, interviews and documentation studies. This study was conducted during a one-month stay in Berakit Village. Based on the results and discussion, the findings of this study are that the indigenous knowledge of the Laut Tribe community in Panglong Village has begun to shift into assimilation with Malay ethnic culture on the mainland of Panglong Village. Meanwhile, the knowledge of the sea tribe that is synonymous with bekajang has begun to change because they live on land.